2020
DOI: 10.1038/s41401-020-0392-8
|View full text |Cite
|
Sign up to set email alerts
|

Aloe-emodin exerts cholesterol-lowering effects by inhibiting proprotein convertase subtilisin/kexin type 9 in hyperlipidemic rats

Abstract: Hyperlipidemia (HPL) characterized by metabolic disorder of lipids and cholesterol is one of the important risk factors for cardiovascular diseases. Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a potent circulating regulator of LDL through its ability to induce degradation of the low-density lipoprotein cholesterol receptor (LDLR) in the lysosome of hepatocytes. Aloe-emodin (AE) is one of potentially bioactive components of Chinese traditional medicine Daming capsule. In this study we evaluated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…Interestingly, aloe ameliorates the liver fat content, and in vitro studies on HepG2 cells show a negative effect on SREBP and HNF1α. As expected, the inhibition of both transcription factors determined a downregulation of PCSK9, associated with increased expression of LDLR and LDL uptake ( Figure 1 ) [ 187 ].…”
Section: Other Inhibitorssupporting
confidence: 64%
See 1 more Smart Citation
“…Interestingly, aloe ameliorates the liver fat content, and in vitro studies on HepG2 cells show a negative effect on SREBP and HNF1α. As expected, the inhibition of both transcription factors determined a downregulation of PCSK9, associated with increased expression of LDLR and LDL uptake ( Figure 1 ) [ 187 ].…”
Section: Other Inhibitorssupporting
confidence: 64%
“…Interestingly, aloe ameliorates the liver fat content, and in vitro studies on HepG2 cells show a negative effect on SREBP and HNF1α. As expected, the inhibition of both transcription factors determined a downregulation of PCSK9, associated with increased expression of LDLR and LDL uptake (Figure 1) [187]. Not known In vitro Not known [191,192] 0.2% 20 20 Oxidation [191,192] Most of the individualized compounds have been shown to inhibit PCSK9 transcription factors, such as SREBP and HNF1α.…”
Section: Emodinmentioning
confidence: 53%
“…Several pharmacological properties on Mandenol have been reported including attenuating the expression of pro-in ammatory factors [41], Gudiya et al have shown that Myricanone was equipped with the biological functions of antioxidant, antiin ammatory, and anti-ischemia-reperfusion injury [42]. In addition, aloe-emodin is a widely existing anthraquinone in nature, which has been found to lower cholesterol by inhibiting PCSK9 [43].…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid metabolism disorders and lipid accumulation in cardiomyocytes result in the release of various cytokines, especially promoting the secretion of leukocyte adhesion molecules and chemokines, culminating in cardiomyocyte damaged and impaired diastolic and systolic functions ( Schilling et al, 2012 ; Jia et al, 2016 ). Recent studies have examined the novel traditional Chinese medicines that may prevent the progression of hyperlipidemia ( Bian et al, 2020 ; Chen et al, 2020 ; Su et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%